2020
DOI: 10.1140/epjp/s13360-020-00608-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel deterministic forecast model for the Covid-19 epidemic based on a single ordinary integro-differential equation

Abstract: In this paper, we present a new approach to deterministic modelling of COVID-19 epidemic. Our model dynamics is expressed by a single prognostic variable which satisfies an integro-differential equation. All unknown parameters are described with a single, timedependent variable R(t). We show that our model has similarities to classic compartmental models, such as SIR, and that the variable R(t) can be interpreted as a generalized effective reproduction number. The advantages of our approach are the simplicity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The types of infectious disease modeling consist of deterministic, stochastic, and phenomenological models. Classical deterministic modeling has been widely used, including by Triampo, Baowan, Tang, Nuttavut, and Doungchawee (2007); Köhler-Rieper, Röhl, and De Micheli (2020), then a comparison between deterministic and stochastic was developed by Olabode, Culp, Fisher, Tower, Hull-Nye, and Wang (2021); Allen and Burgin (2000) to interpret various epidemic models. Meanwhile, the phenomenological model has been developed in previous studies using the logistic growth model and the expansion of the Richards curve model Rosadi (2020, 2022a,b).…”
Section: Introductionmentioning
confidence: 99%
“…The types of infectious disease modeling consist of deterministic, stochastic, and phenomenological models. Classical deterministic modeling has been widely used, including by Triampo, Baowan, Tang, Nuttavut, and Doungchawee (2007); Köhler-Rieper, Röhl, and De Micheli (2020), then a comparison between deterministic and stochastic was developed by Olabode, Culp, Fisher, Tower, Hull-Nye, and Wang (2021); Allen and Burgin (2000) to interpret various epidemic models. Meanwhile, the phenomenological model has been developed in previous studies using the logistic growth model and the expansion of the Richards curve model Rosadi (2020, 2022a,b).…”
Section: Introductionmentioning
confidence: 99%
“…We identified several attempts to propose and apply models with mathematical expressions. These includes classical compartmental models [ 12 ] alongside Erlang models [ 13 ], integrodifferential equations to simulate infection process [ 14 , 15 ], delay-differential equations to include latency period [ 16 ], partial differential equations for spatial heterogeneity [ 17 , 18 ], and meta-populations for age-directed control strategies [ 19 ]. Also, we found that there are several mathematical models formulated in multiple countries to understand the complex transmission pattern of the COVID-19 pandemic [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…A deterministic model based on SIR framework was proposed to understand the evolution of COVID-19 outbreaks during lockdown and social distancing policy in Germany and Italy by Ianni and Rossi [ 57 ]. Similarly, Köhler-Rieper et al [ 58 ] proposed a new approach to mathematical modelling of COVID-19 transmission dynamics by constructing a single ordinary integro-differential equation. It was shown that the model has similarities with the classical SIR model, and capable of predicting the disease outbreaks for a period of about 4 weeks.…”
Section: Introductionmentioning
confidence: 99%